High Prevalence of Vaginal and Rectal Mycoplasma genitalium Macrolide Resistance Among Female Sexually Transmitted Disease Clinic Patients in Seattle, Washington. Issue 5 (May 2020) - Khosropour, Christine M.; Jensen, Jørgen S.; Soge, Olusegun O.; Leipertz, Gina; Unutzer, Anna; Pascual, Rushlenne; Barbee, Lindley A.; Dombrowski, Julia C.; Golden, Matthew R.; Manhart, Lisa E.
Abstract : Background: Rectal Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) are increasingly recognized as common infections among women. Little is known about the prevalence of rectal Mycoplasma genitalium (MG), rectal MG/CT/GC coinfection, or MG antimicrobial resistance patterns among women. Methods: In 2017 to 2018, we recruited women at high risk for CT from Seattle's municipal sexually transmitted disease clinic. Participants self-collected vaginal and rectal specimens for CT/GC nucleic acid amplification testing. We retrospectively tested samples for vaginal and rectal MG using nucleic acid amplification testing and tested MG-positive specimens for macrolide resistance-mediating mutations (MRM) and ParC quinolone resistance-associated mutations (QRAMs). Results: Of 50 enrolled women, 13 (26%) tested positive for MG, including 10 (20%) with vaginal MG and 11 (22%) with rectal MG; 8 (62%) had concurrent vaginal/rectal MG. Five (38%) were coinfected with CT, none with GC. Only 2 of 11 women with rectal MG reported anal sex in the prior year. Of MG-positive specimens, 100% of rectal and 89% of vaginal specimens had an MRM. There were no vaginal or rectal MG-positive specimens with ParC QRAMs previously associated with quinolone failure. Five MG-infected women received azithromycin for vaginal CT, 4 of whom had a MG MRM detected in their vaginal and/or rectal specimens. Conclusions: We observed a high prevalence of macrolide-resistant vaginal and rectal MG among a population of women at high risk for CT. This study highlights how the use of antimicrobials designed to treat an identified infection—in this case, CT—could influence treatment outcomes and antimicrobial susceptibility in other unidentified infections. Abstract : Twenty-six percent of female sexually transmitted disease clinic patients tested positive for either vaginal or rectal Mycoplasma genitalium . All rectal specimens and 89% of vaginal specimens were macrolide resistant.Supplemental digital content is available in the text.